Diksi dan gaya bahasa janturan wayang kulit purwa lakon parta krama oleh dalang Ki Anom Suroto: kajian stilistika - Jati, Purbo Asmoro; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
The goal of this research is describing the use of diction and style of language in the wayang kulit wayang kulit Purwa Lakon Parta Krama by Dalang Ki Anom Suroto using stylistic studies. The research method used is descriptive qualitative method. The data source for this research is the transcript of the song derived from the recording of the script for the YouTube video of wayang kulit purwa for the Parta Krama play by the puppeteer Ki Anom Suroto. The data used in this study are phrases, words and sentences that have a relationship with diction and style of language. Data collection techniques are listening, listening, and transcription techniques. Furthermore, the collected data were then analyzed using data reduction techniques, data display as well as drawing conclusions and verification. Based on the results of the analysis of the results of research on the use of diction and language style of wayang kulit Purwa Lakon Parta Krama by Dalang Ki Anom Suroto, it shows that there are dictions used, namely 4 tembung dwilingga data, and 8 tembung dwipurwa data which are used to emphasize words in jants puppet. Word repetition gives meaning and rhythmic pressure in the array, as well as provides sound pressure that can beautify sentences for words that contain repetition patterns. Then there are 3 garba data used in abbreviating words to provide efficiency to sentences. The style of language found in this study is 1 data style of comparative metaphor characterized by the impression of comparing one thing with another thing, there are 3 data of style of hyperbole parable, which is characterized by the impression of exaggerating something, and there is 1 data of repetition style of language Alliteration is characterized by the repetition of consonant sounds.